Sejarah Perkembangan Islam di Amerika - Khalik, Subhan (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
Certainly not found records of the beginning of the arrival of Islam in America, but some experts concluded that Islam arrived in America with the arrival of migrants from African slaves that occurred around the sixteenth century until the eighteenth century. Post-bombing of the WTC in 2001, Muslims in America are within tolerance threshold and receive treatment less commendable than the government and the local population. But gradually a similar treatment to decrease with the level of curiosity of the American public against the teachings of Islam. It is said that the best-selling book in America today is the Qur’an and the trigger of all of it is one- sided information to discredit the government and the desire of Islam, it gives birth to generations curious about Islam and then make Islam as an alternative religion.